Does the Medium Matter? Evaluating the Depth of Reflective Writing by Medical Students on Social Media Compared to the Traditional Private Essay Using the REFLECT Rubric - Alisha Brown; Joshua Jauregui; Jonathan S. Ilgen; Jeff Riddell; Douglas Schaad; Jared Strote; Jamie Shandro (Western Journal of Emergency Medicine, 2019)
Introduction: Social media is a novel medium to host reflective writing (RW) essays, yet its impact on depth of students’ reflection is unknown. Shifting reflection on to social platforms offers opportunities for students to engage with their community, yet may leave them feeling vulnerable and less willing to reflect deeply. Using sociomateriality as a conceptual framework, we aimed to compare the depth of reflection in RW samples submitted by medical students in a traditional private essay format to those posted on a secure social media platform. Methods: Fourth-year medical students submitted a RW essay as part of their emergency medicine clerkship, either in a private essay format (academic year [AY] 2015) or onto a closed, password-protected social media website (AY 2016). Five raters used the Reflection Evaluation for Learners’ Enhanced Competencies Tool (REFLECT) to score 122 de-identified RW samples (55 private, 67 social media). Average scores on two platforms were compared. Students were also surveyed regarding their comfort with the social media experience. Results: There were no differences in average composite REFLECT scores between the private essay (14.1, 95% confidence interval [CI], 12.0–16.2) and social media (13.7 95% CI, 11.4–16.0) submission formats (t [1,120] = 0.94, p = 0.35). Of the 73% of students who responded to the survey, 72% reported feeling comfortable sharing their personal reflections with peers, and 84% felt comfortable commenting on peers’ writing. Conclusion: Students generally felt comfortable using social media for shared reflection. The depth of reflection in RW essays was similar between the private and social media submission formats.